Concurrent Hypoparathyroidism Is Associated With Impaired Physical Function and Quality of Life in Hypothyroidism. (31st March 2016) - Sikjaer, Tanja; Moser, Emil; Rolighed, Lars; Underbjerg, Line; Bislev, Lise Sofie; Mosekilde, Leif; Rejnmark, Lars
ABSTRACT: Total thyroidectomy causes postsurgical hypothyroidism (HypoT). Besides HypoT, as a complication patients may also develop hypoparathyroidism (HypoPT). The aim of this study was to assess quality of life (QoL), muscle function, and postural stability in patients with postsurgical hypothyroidism and hypoparathyroidism (HypoT+PT) as compared to patients with postsurgical HypoT and healthy controls. Age‐ and gender‐matched patients on treatment for HypoT+PT and HypoT were recruited from our outpatient clinic. Matched healthy controls were recruited from the general background population. Compared with controls, HypoT was associated with a significantly lower mental summary score, whereas patients with HypoT+PT had a significantly lower physical summary score (Short Form 36 Health Survey questionnaire version 2). Moreover, the physical component score was significantly lower in patients with HypoT+PT compared with HypoT. WHO‐5 well‐being index was significantly lower in both groups of patients compared with controls, but did not differ between groups of patients. Compared with controls, muscle strength and maximal force production was significantly reduced in HypoT+PT, but not in HypoT. In HypoT+PT, the time spent on the Timed Up & Go test and the Repeated Chair Stands test were significantly longer than in the HypoT group and the control group. Postsurgical HypoT+PT is associated with a more severe impairment of QoL, in particular regarding physical functioning, than HypoT. HypoT+PT patients are also hampered by impaired muscle function. Studies on how to improve well‐being and muscle function in HypoT+PT patients are warranted. © 2016 American Society for Bone and Mineral Research.